Evaluation of the Graduate Profile and the Achievement of Competences for the Institutional Accreditation - Espinoza-Narcizo, Arnostron E. (2020)
The objective of the investigation was to determine the relationship between the evaluation of the Graduate Profile with the Achievement of the Competences for the Accreditation of the Second Professional Specialty Program of official students of the Peruvian Navy, Lima Peru. Method: the study was quantitative, descriptive - correlational. For data collection, two instruments were prepared with a sample of 10 students, using an opinion survey of official students using the value scale: Average 1, Superior Average 2 and Superior Average 3. For hypothesis testing, Pearson's correlation, achieving a high positive correlation for each dimension of the study. Result: the study carried out has shown that there is a direct and significant relationship between the evaluation of the graduate's profile and the achievement of the skills for Accreditation of the Second Specialty Program at a significance level of 5% and a p-value = 0.000 <0.05 , concluding that the evaluation of the Graduate Profile positively influences the Program Accreditation.